Factors Associated with the Low Coverage of Tetanus Toxoid Immunization in Pregnant Women in the Working Area of Puskesmas Pinembani - Mery, Mery; Afni, Nur; Amalinda, Finta (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
Tetanus toxoid immunization is a process to build immunity to prevent tetanus infection. Tetanus toxoid immunization in pregnant women provides immunity to the fetus against tetanus infection (Tetanus neonaturum) during labor and postnatally. The purpose of this study was to determine the factors for the low coverage of tetanus toksoidimmunization consisting of knowledge, the role of health workers, and Distance. This type of research is analytical survey research with a cross-sectional approach. This research was conducted in the Pinembani Community Health Center's work area in June 2020, with a sample of 41 respondents. The results showed no relationship between knowledge and coverage of Tetanus toxoid immunization, as evidenced by statistical tests with a p-value of 0.178> 0.05. The results showed a connection between health workers' role and Tetanus toxoid immunization coverage, as evidenced by statistical tests with a p-value of 0.003 <0.05. The results showed no relationship between distance and tetanus toxoid immunization coverage, as evidenced by statistical tests with a p-value of 0.073> 0.05. This research is expected for health workers in the working area of Puskesmas Pinembani always to survey the Tetanus Toxic Immunization service and provide more counseling or information about health at the posyandu to increase the knowledge of pregnant women.